Training teachers of professional ethics in nursing schools - Spagnolo, A. G.; Di Pietro, M. L.; G. (Medicina e Morale, 1991)
The nursing profession is trying to find a specific role in health professions, in order to have a specific identily, but stili closely connected to the medical profession. Nurses and other health workers are somewhat perplexed by a recent Italian bill on the reorganization of the nursing profession. The authors deal with the point in the bill that takes teaching professional ethics in nursing schools into consideration. The bill states that every nurse with the Italian professional level of "AFD" or "DAI'' should be qualified to teach professional ethics. However, the authors believe that this level of education is not sufficient for such a delicate subject. They therefore propose the creation of a specific academic course in order to go deeper into the various ethical problems. which should be considered within the wider ficld of bioethics. The course is to reach an ethics in nursing schools.